A NEW SPECIES OF MALVACIPHYLLUM (MALVACEAE: MALVOIDEAE) FROM INLAND PALEOCENE RAINFORESTS OF COLOMBIA (Ameghiniana, 2026)
Malvoideae, the largest subfamily within Malvaceae, have a distinct fossil record in South America extending back to the Paleocenerainforests of the Cerrejón Fm. in Colombia. We describe Malvaciphyllum checuorum sp. nov., a second species of fossil leaf with affinities to Malvoideae, based on leaf impressions from the Paleocene (Selandian) Bogotá Formation in Colombia. Sixty-two leaf impressions of Malvaceae (informal morphotype BF4) were examined. Leaf characters were compared to previously described taxa and affinities to Malvoideae were supported based on the identification of synapomorphic traits of the subfamily. This record is the second species of Malvaciphyllum described from the Paleocene of Colombia and likely occupied the most inland terra firme conditions of the earliest Neotropical forests.